PENGARUH PEMBERIAN JINTEN HITAM (Nigella Sativa) SEBAGAI IMUNOMODULATOR DALAM AIR MINUM TERHADAP PROFIL DARAH (Hemoglobin dan Hematokrit) BROILER BETINA - Diana Melia; Siswanto Siswanto; Purnama Edy Santosa; Sri Suharyati (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2021)
This study aimed to determine the levels of hemoglobin and hematocrit and the best dose of Nigella sativa to the blood profile of female broilers. This research was conducted in December 2019 - January 2020 at the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. Checking hemoglobin and hematocrit levels was carried out at Pramitra Biolab Indonesia. This study used 60 female broilers, using a completely randomized design (CRD) with four treatments and each treatment was repeated three times, namely drinking water without a mixture of Nigella sativa (P0), drinking water with 36 mg / kg / w / day Nigella sativa (P1 ), drinking water with 72 mg / kg / body weight / day Nigella sativa (P2), drinking water with 144 mg / kg / body weight / day Nigella sativa (P3). Based on the data obtained from the observation results was arranged in the form of simple tabulation and displayed in the form of a histogram , and analyzed descriptively. The results showed that giving Nigella sativa in drinking water had an effect on hemoglobin levels and the hematocrit value of female broilers. Hemoglobin and hematocrit levels in each treatment were still in the normal range and the optimal dose of Nigella sativa for the blood profile of female broiler chickens which was found in P2 (provision of drinking water at a dose of 72 mg / kg BW / day Nigella sativa). Keyword s: Broiler Females, Hematocrit, Hemoglobin, Immunomodulator, Nigella sativa